AMBIGUITY IN JAVANESE DIALOGUE OF YO WIS BEN: A CROSS-LINGUISTIC ANALYSIS WITH ENGLISH - M. Iqbal Farabi Sufi; Khanandya Nila Ulfah; Deliana Deliana (Universitas HKBP Nommensen, 2026)
This study explores how ambiguity functions in the Javanese dialogue of the Yo Wis Ben film series, focusing on its lexical and structural forms and their comparative interpretation in English. Employing a qualitative descriptive approach and content analysis, eight scenes were analyzed using Lyons’ (1977) framework of ambiguity. The findings show that lexical ambiguity, where a word carries multiple unrelated meanings, appears more frequently than structural ambiguity, which arises from flexible syntactic constructions. Expressions such as singo, yo wis ben, pedhot, and legi illustrate how Javanese speakers use ambiguity to produce humor and manage social relations. Theoretically, the study extends pragmatic and cross-linguistic perspectives by demonstrating that ambiguity in Javanese is not linguistic confusion but a deliberate communicative strategy reflecting high-context interaction. Practically, it offers insights for translation, intercultural communication, and media discourse analysis, emphasizing how local-language films employ ambiguity to convey cultural identity, humor, and interpersonal nuance in multilingual contexts.